Use of reconstructed 3D VMEC equilibria to match effects of toroidally rotating discharges in DIII-D. (13th October 2016) - Wingen, A.; Wilcox, R.S.; Cianciosa, M.R.; Seal, S.K.; Unterberg, E.A.; Hanson, J.M.; Hirshman, S.P.; Lao, L.L.; Logan, N.C.; Paz-Soldan, C.; Shafer, M.W.
Abstract: A technique for tokamak equilibrium reconstructions is used for multiple DIII-D discharges, including L-mode and H-mode cases when weakly 3D fields ( δ B / B ∼ 10 − 3 ) are applied. The technique couples diagnostics to the non-linear, ideal MHD equilibrium solver VMEC, using the V3FIT code, to find the most likely 3D equilibrium based on a suite of measurements. It is demonstrated that V3FIT can be used to find non-linear 3D equilibria that are consistent with experimental measurements of the plasma response to very weak 3D perturbations, as well as with 2D profile measurements. Observations at DIII-D show that plasma rotation larger than 20 krad s −1 changes the relative phase between the applied 3D fields and the measured plasma response. Discharges with low averaged rotation (10 krad s −1 ) and peaked rotation profiles (40 krad s −1 ) are reconstructed. Similarities and differences to forward modeled VMEC equilibria, which do not include rotational effects, are shown. Toroidal phase shifts of up to 30 ° are found between the measured and forward modeled plasma responses at the highest values of rotation. The plasma response phases of reconstructed equilibra on the other hand match the measured ones. This is the first time V3FIT has been used to reconstruct weakly 3D tokamak equilibria.